Clinical evaluation of medicines for patients with mild cognitive impairment and mild dementia due to Alzheimer's disease in Japan - Reiko Yanagihara (Alzheimer’s & Dementia: Translational Research & Clinical Interventions, 2025)
Abstract Lecanemab and donanemab were approved in Japan in September 2023 and September 2024, respectively, for the treatment of patients with mild cognitive impairment and mild dementia due to Alzheimer's disease. Evaluating the efficacy of these drugs requires demonstrating a clinically meaningful delay in symptom progression while ensuring an acceptable safety profile. This paper describes the efficacy assessment in the Pharmaceuticals and Medical Devices Agency's (PMDA) review, focusing on clinical endpoints, biomarker evaluations, and the role of minimal clinically important difference (MCID) in benefit–risk assessment. At present, the Clinical Dementia Rating Sum of Boxes (CDR‐SB), which assesses both cognitive and functional decline, is one of the most recommended primary endpoints in confirmatory trials. Time‐to‐progression analysis should be also conducted to support clinical significance. Biomarker evaluations, particularly amyloid beta (Aβ) reduction, should be included as secondary endpoints to confirm the mechanism of action. Though biomarker assessments showed significant Aβ reduction for both anti‐amyloid therapies, no direct correlation with clinical outcomes was observed, limiting their use as surrogate endpoints. Therefore, the MCID for clinical symptom progression suppression cannot be inferred based on Aβ reduction. Safety evaluation focused on amyloid‐related imaging abnormalities (ARIAs), a key risk associated with anti‐Aβ antibody treatments. Under the condition in which ARIA risk is managed through magnetic resonance imaging monitoring and predefined risk mitigation measures, PMDA considers the benefit–risk balance of these anti‐amyloid therapies are favorable. While regulatory approval does not require meeting predefined MCID thresholds, it is based on a comprehensive benefit–risk assessment. For regulatory approval, future drugs will be required to demonstrate a benefit–risk balance equivalent to or more favorable than that of the approved anti‐Aβ antibody drugs. Highlights Lecanemab and donanemab were approved in Japan for early Alzheimer's disease in 2023 and 2024, respectively. Drug efficacy was considered clinically meaningful after comprehensive evaluation. Biomarker evaluation, including amyloid beta (Aβ), is crucial to support the intended mechanism of action. Aβ reduction did not correlate with the suppression of clinical symptom progression in individual cases. No biomarker is validated as a surrogate, and minimal clinically important difference cannot be inferred from Aβ reduction.